Non-alcoholic fatty liver disease after liver transplantation: A lifestyle reloaded - Lubomir Skladany; Jana Badinkova; Svetlana Adamcova-Selcanova (Kazimierz Wielki University, 2017)
BACKGROUND AND AIMS Apart from non-alcoholic steatohepatitis (NASH) as the sole etiology behind liver transplantation (LTx), non-alcoholic fatty liver disease (NAFLD)/NASH can play an important role in all the remaining etiologies of LTx. To gauge such a contribution of NAFLD/NASH, authors made use of 2 assumptions: a) there is tendency post-LTx to regain body shape (including obesity and its metabolic consequences) patients (pts) had before decompensation of their liver disease, therefore b) post-LTx fatty liver index (FLI) ≥ 60 (sensitivity/specificity for  NAFLD>85%) might reflect NAFLD pre-LTx.   METHODS a) A retrospective study of body mass index (BMI) in the 6th and 12th moths (m) after LTx, b) a cross-sectional study of  FLI (and ultrasonography) > 6 m after LTx (Jana Badinková (JB), october 2015). a) An analysis of the medical records of pts after LTx performed in transplantation centre (TC) Banska Bystrica (BB). Interval studied: January 2011 - march 2016 (JB). Source of data: Hospital Information System (Care Centre® Copyright 2000, CGM, Version 3.33.2). Inclusion criteria: LTx in TC BB > 6 m ago. Exclusion criteria: LTx due to NASH; insufficient data for a FLI calculation. b) All the pts selected by inclusion/exclusion criteria were contacted by a TC physician (JB) via mobile phone (text message, or phone call) in order to determine current waist circumference.  Recorded variables: gender; age; etiology of advance chronic liver disease; BMI; ultrasonography; FLI (triacylglycerides, gamma-glutamyltransferase, waist circumference (cm), height (m), weight (kg)). Overweight was defined as a BMI > 25 kg/m2, obesity as a BMI > 30. An FLI > 60 was the value that indicated NAFLD. RESULTS From January 2011 to December 2015, 90 pts underwent LTx in TC BB. The inclusion  criteria were met by 87 of them, 40 pts were subsequently excluded. The cohort for final analysis consisted of 47 pts. Average age - 51 years (22-65); women - 25 (53%); indications for LTx: alcoholic liver disease - 22 pts (46%), autoimmune hepatitis - 7 pts (15%), primary sclerosing cholangitis - 6 pts (13%), primary biliary cholangitis - 5pts (11%), chronic hepatitis C - 3 pts (6,5%), chronic hepatitis B - 3pts (6,5%), other - 1 pt (2%). Average time from LTx to FLI measurement was 33 m (6-53). Overweight, and obesity 6 m after LTx: 22 pts (47%), and 5 pts (11%), respectively; 12 m after LTx - 21 pts (45%), and 9 pts (19%), respectively. FLI > 60 was found in 20 pts (43%). Twelve of 20 pts (60%) with FLI > 60 had an ultrasonography without the signs of steatosis.  CONCLUSIONS Provided the validity of assumptions that a) LTx restores pre-LTx-pre-decompensation body shape, and therefore b) FLI post-LTx is similar to FLI pre-LTx-pre-decompensation, the real contribution of NAFLD/NASH to LTx burden could be much greater than that derived from isolated NASH-LTx numbers. In this small cohort of pts transplanted for non-NASH etiologies, pre-LTx NAFLD could have been present in as much as 43% of pts.